Mechanism and properties of coloured nanoscale SiO2 prepared from silica and reactive dyes. (18th July 2016) - Zhang, Liping; Li, Min; Tian, Anli; Fu, Shaohai
Abstract : KH560‐modified SiO2 was prepared using tetraethyl orthosilicate (TEOS) and γ‐(2, 3‐epoxypropoxy) propytrimethoxysilane (KH560) by the sol–gel method and then coloured with CI Reactive Blue 4 (X‐BR) to prepare coloured nanoscale SiO2 . The antisolvent performance and the results of cross‐polarisation/magic angle spinning 13 C nuclear magnetic resonance and Fourier transform infrared spectroscopy showed that the reaction of X‐BR with KH560‐modified SiO2 is a two‐step process: X‐BR is firstly adsorbed by KH560‐modified SiO2 via van der Waals forces, and then nucleophilic substitution occurs between dichloro triazine and the epoxy group. The grafting ratio of X‐BR on KH560‐modified SiO2 reached 95% under optimum conditions, i.e. a mass ratio of KH560 to TEOS of 20%, a temperature of 40 °C, a pH of 8.5, and a reaction time of 5 h. X‐ray diffraction analysis and transmission electron microscopy showed that the coloured nanoscale SiO2 was amorphous, with a mean diameter of 216 nm. Experimental application showed that the coloured nanoscale SiO2 had excellent stability to solvents and alkaline solution, and the absorptive capacity of the coloured nanoscale SiO2 in the 200–400 nm region was higher than that of X‐BR. The light fastness of the coloured nanoscale SiO2 reached 5–6 grade.